Lifestyle and Psychological Factors Associated with Body Weight Status among University Students in Malaysia - Mokhtari, Tahereh; Jamaluddin, Rosita; Saad, Hazizi Abu (Pakistan Journal of Nutrition, 2014)
This study was conducted to determine the factors associated with body weight status among university students. Socio-demographic, lifestyle, dietary and psychological factors are elements that can impact on students’ weight status. The main aim of this study is bringing to light the effects of the above-mentioned factors on adult students’ weight status. The school of graduate studies of the Universiti Putra Malaysia randomly selected 500 students through iGIMS, however, only 310 Iranian students participated in this study. The data was collected through a 4-section questionnaire and anthropometric measurements such as height and weight were obtained for calculating body mass index (BMI). The results indicated a significant relationship between BMI and energy intake, carbohydrate, protein, fat, physical activity and smoking status, smoking duration, anxiety, age, level of education, gender, marital status and income level of the respondents. Multivariate regression analysis for the prediction of body weight status demonstrated that gender, carbohydrate, age, physical activity, anxiety, income level and smoking status had significant relationships with BMI. In conclusion, the etiology of obesity and overweight is complex and there are a large number of factors it is affected by including energy intake, physical activity, psychological status, environment, culture and economic status. Investigation of the factors associated with body weight status is a necessary consideration in planning obesity interventions.